2022
DOI: 10.1038/s41397-022-00281-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of Clozapine-induced agranulocytosis: a systematic review and meta-analysis

Abstract: Although clozapine is the most effective pharmacotherapy for treatment-resistant schizophrenia, it is under-utilized, and initiation is often delayed. One reason is the occurrence of a potentially fatal adverse reaction, clozapine-induced agranulocytosis (CIA). Identifying genetic variations contributing to CIA would help predict patient risk of developing CIA and personalize treatment. Here, we (1) review existing pharmacogenomic studies of CIA, and (2) conduct meta-analyses to identify targets for clinical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…For antipsychotic-induced tardive dyskinesia, two meta-analysis studies reported in a mixed population, Caucasians and Asians separately [ 57 , 58 ], and the other two reported in mixed populations only [ 59 , 60 ]. One meta-analysis study reported clozapine-induced agranulocytosis in mixed populations [ 61 ]. For antipsychotic exposure (pharmacokinetics), one meta-analysis study reported in a mixed population and Asians [ 62 ], while the other two reported in a mixed population only [ 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For antipsychotic-induced tardive dyskinesia, two meta-analysis studies reported in a mixed population, Caucasians and Asians separately [ 57 , 58 ], and the other two reported in mixed populations only [ 59 , 60 ]. One meta-analysis study reported clozapine-induced agranulocytosis in mixed populations [ 61 ]. For antipsychotic exposure (pharmacokinetics), one meta-analysis study reported in a mixed population and Asians [ 62 ], while the other two reported in a mixed population only [ 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Islam et al performed meta-analyses on 13 variants across nine genes ( NQO2, CYBA, MPO, HLA-DRB1, HLA-DQB1, HLA-DRB4, HLA-DRB5, HLA-DR2, and HLA-B ) and CIA, defined by ANC< 500/μL [ 61 ]. Only the association between HLA-DRB1 *04:02 and CIA remained significant after the application of the Bonferroni correction when carriers were compared to non-carriers (pooled OR: 5.89, 95% CI: 2.20, 15.80, two original studies) ( Supplementary Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, antipsychotic medications are associated with increased incidence of ADRs, such as clozapine, which makes it a drug requiring mandatory full-blood count monitoring due to the risk of neutropenia and agranulocytosis 38 . A meta-analysis demonstrated that individuals carrying the HLA-DRB1*04:02 allele had nearly sixfold-higher odds of clozapine-induced agranulocytosis 39 . In addition, a recent retrospective study found that, in a cohort of patients taking clozapine, 4.3% reported minor neutropenia and 1.2% reported serious neutropenia leading to cessation of clozapine 40 .…”
Section: Discussionmentioning
confidence: 99%
“…By adding SLCO variants, the expected test sensitivity increased, whereas the specificity decreased (89.0%–86.9%) still increasing the overall risk predictability ( Ninomiya et al ). Incorporating new SLCO variants to pre-emptively assess CIAG risk improved the effectiveness of PGx-guided clozapine administration: SNP-based predictive tests differ between ancestral groups due to alleles or haplotypes frequencies and varying patterns of linkage disequilibrium ( Islam et al, 2022 ).…”
mentioning
confidence: 99%